Keberlakuan KUHP dan Qanun Jinayat terhadap Tindak Pidana Pencabulan di Aceh (Studi Putusan Nomor: 417/Pid.B/2018/Pn.Jth) - Perdana, Andry Bhakti (Al-Jinayah : Jurnal Hukum Pidana Islam, 2020)
Penal Code is a material law applicable to any person who commits a crime in the state. Meanwhile, the criminal law of Aceh (Qanun Jinayat Aceh) is material law applies specifically to every person who is Muslim and who has committed a crime within the jurisdiction of the Aceh Province. In Decision Number 417 / Pid.B / 2018 / PN.Jth the defendant was sentenced by the judge to imprisonment for the indecent acts against the victim under Article 289 of the Criminal Code, the case also comes under Article 46 of the criminal law of Aceh (Qanun Jinayat Aceh). Thus, this paper aims to analyze the defendant's actions under Article 289 of the Penal Code of Indonesia and Article 46 of the criminal law of Aceh (Qanun Jinayat Aceh), as well as the court's decision. It concluded that: First, the defendant's actions are more under Article 46 of the criminal law of Aceh (Qanun Jinayat Aceh) regarding sexual harassment. Secondly, applying the case under the Penal Code is inappropriate because the public prosecutor overlook the principle of criminal law, namely; lex specialis derogate legi Generali in formulating a criminal act.